2020
DOI: 10.3389/fimmu.2020.543022
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Stress and Intestinal Inflammation: A Perilous Union

Abstract: The intestinal tract encompasses the largest mucosal surface fortified with a fine layer of intestinal epithelial cells along with highly sophisticated network of the lamina propria immune cells that are indispensable to sustain gut homeostasis. However, it can be challenging to uphold homeostasis when these cells in the intestine are perpetually exposed to insults of both endogenous and exogenous origin. The complex networking and dynamic microenvironment in the intestine demand highly functional cells ultima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 107 publications
0
24
0
Order By: Relevance
“…Unresolvable ER stress leads to inflammatory responses (Eugene et al, 2020) and inflammation is another pathological feature of L-arginine-induced AP (El Morsy and Ahmed, 2020; Abdelzaher ,B, immunohistochemical staining of F4/80 and CD11b showed that there was a large amount of macrophage infiltration in the pancreatic tissue of L-arginine treated mice, and intraperitoneal injection of 20 μg/kg-MFG-E8 effectively reduced the degree of macrophage infiltration (p < 0.05). Gr1 and MPO-labeled neutrophils showed the same trend as macrophages, suggesting that exogenous MFG-E8 effectively reduced the number of inflammatory cells in the pancreatic tissue (p < 0.05, Figures 3A,B).…”
Section: Mfg-e8 Alleviates the Inflammatory Response In Experimental-...mentioning
confidence: 99%
“…Unresolvable ER stress leads to inflammatory responses (Eugene et al, 2020) and inflammation is another pathological feature of L-arginine-induced AP (El Morsy and Ahmed, 2020; Abdelzaher ,B, immunohistochemical staining of F4/80 and CD11b showed that there was a large amount of macrophage infiltration in the pancreatic tissue of L-arginine treated mice, and intraperitoneal injection of 20 μg/kg-MFG-E8 effectively reduced the degree of macrophage infiltration (p < 0.05). Gr1 and MPO-labeled neutrophils showed the same trend as macrophages, suggesting that exogenous MFG-E8 effectively reduced the number of inflammatory cells in the pancreatic tissue (p < 0.05, Figures 3A,B).…”
Section: Mfg-e8 Alleviates the Inflammatory Response In Experimental-...mentioning
confidence: 99%
“…However, we did not analyze the local effects of peritonitis. Several studies have already highlighted the relevance of intestinal ER stress in peritonitis that is tightly linked to deranged intestinal tissue homeostasis and immunity ( 51 , 52 ), and particularly the impairment of the intestinal barrier function ( 53 ). Further studies will be necessary to clarify the source or the nature of the compounds that trigger the ER stress/UPR and inflammatory response in the liver.…”
Section: Discussionmentioning
confidence: 99%
“…Continual exposure to dietary metabolites, toxins impeded, exogenous antigens, and gut microflora makes the intestine susceptible to invasion by exogenous stress, ultimately burdening the ER resulting in ER stress ( 45 ). Unresolved ER stress can be the primary cause of inflammation in the intestine ( 46 , 47 ).…”
Section: Discussionmentioning
confidence: 99%